Evaluation Of Vehicle Transportation System At KMP Merak On The Siwa - Tobaku Track - Purboyo Purboyo; Irwan Irwan; Pierre Marcello Lopulalan (IWJ : Inland Waterways Journal, 2023)
Siwa Ferry Port with 3 units of ships, namely KMP New Rose, KMP New Camellia and KMP Merak, with the Siwa - Tobaku crossing service having an important role for regional development in Wajo Regency and several surrounding areas. In managing the Siwa Ferry Port, the Regional Government of Wajo Regency as the port operator, together with the Region XIX Land Transportation Management Center of South Sulawesi and West Sulawesi Provinces as regulator functions always supervise aspects of safety, security and order. The research method used is direct observation in the field (Field Research) by measuring the distance between vehicles and lashing tools as well as literature/documentation. This research analysis is guided by the Regulation of the Minister of Transportation Number 115 of 2016 regarding Procedures for Transporting Vehicles on Ships and the Regulation of the Minister of Transportation Number 30 of 2016 regarding Obligations to Bind Vehicles to Crossing Transport Vessels. The analysis that will be used is the analysis of vehicle weighing equipment needs, analysis of vehicle placement on ships, analysis of vehicle loading space cleanliness, analysis of the distance between vehicles, analysis of vehicle loading space sterilization from passengers, analysis of vehicle binding and analysis of administrative sanctions to ship operators. Based on this analysis, it was concluded that the conditions of transportation at the Siwa ferry port are still not in accordance with the Regulation of the Minister of Transportation Number 30 of 2016 and Regulation of the Minister of Transportation Number 115 of 2016 in terms of vehicle binding, range between vehicles, sterility of loading space from passengers and spills of grease and oil, availability of fasteners and binding officers.